ANALISIS KEPUASAN NASABAH PT CIMB NIAGA CABANG PANGKALPINANG DENGAN MENGGUNAKAN METODE SERVICE QUALITY (SERVQUAL) - Yanuar, Yadi; Lestari, Deara Shinta; Novika (Jurnal Progresif Manajemen Bisnis, 2020)
The banking sector plays an important role in development efforts the economic sector. In addition, banks are also tasked with collecting and distributing public funds to improve people’s lives. At technology that resulted in extraordinary changes. Easy of access to obtain information from the media makes competition between bank’s very tight, resulting in more customers choosing the type of bank to be used for transactions. This study aims to determine how the level of customer satisfaction with the services provided by PT CIMB Niaga Pangkalpinang Branch. The results of the study, showed that the overall value of GAP was negative. In this case the customer is still unsatisfied with the services provided by CIMB Niaga Pangkalpinang branch. There is the highest GAP value on the X1 variable that is -0,83 and the lowest value on the X5 variable is -0,40.